Fundamentals of Turbomachines - Dick, Erik.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This textbook explores the working principles of all kinds of turbomachines. The same theoretical framework is used to analyze the different machine types. The order in which the different kinds are treated is chosen by the possibility of gradually building up theoretical concepts. For each of the turbomachine kinds, a balance is sought between fundamental understanding and knowledge of practical aspects. Readers are invited through challenging exercises to consider how the theory applies to particular cases. This textbook appeals to senior undergraduate and graduate students in mechanical engineering and to professional engineers seeking to understand the operation of turbomachines. Readers will gain a fundamental understanding of turbomachines and will be able to make a reasoned choice of a turbomachine for a particular application. .
Working Principles -- Basic Components -- Fans -- Compressible Fluids -- Performance Measurement -- Steam Turbines -- Dynamic Similitude -- Pumps -- Hydraulic Turbines -- Wind Turbines -- Power Gas Turbines -- Thrust Gas Turbines -- Axial Compressors -- Radial Compressors -- Axial and Radial Turbines for Gases -- References -- Index.
Keywords: Mechanical engineering; Fluid mechanics; Mechanics; Physics; Thermodynamics; Mechanical Engineering; Engineering Fluid Dynamics; Classical Mechanics; Classical and Continuum Physics; Thermodynamics; Turbomachines; Turbines